KAJIAN KRITIS KETENTUAN WAKTU TUNGGU (IDDAH) DALAM RUU HMPA BIDANG PERKAWINAN - Wahyudi, Muhamad Isna (Jurnal Hukum dan Peradilan, 2016)
There are some provisions of Bill on the Religious Courtsâ€™ Material Law on marriageÂ that need to be formulated in accordance with the current conditions. In this way, theÂ Islamic Marriage Law in Indonesia will become progressive and not discriminativeÂ against women. This article is the continuation of the article entitled â€œMenuju HukumÂ Perkawinan Islam Progresifâ€ which is published in Jurnal Hukum dan Peradilan volumeÂ 3, number 1, March 2014. In this article, the author tries to offer reinterpretation on theÂ provision of waiting period (â€˜iddah) in accordance with the current context. As the result,Â the waiting period should bind both widow and widower.Keywords : waiting period, sex, gender, equality